Moving Santam Insurance Towards Industry 4.0 Through Dynamic Simulation Resource Scheduling - Des Fontaine, R.A. (Rulé) (University of Pretoria. Faculty of Engineering, Built Environment and Information Technology. Dept. of Industrial and Systems Engineering, 2019)
Thesis (B Eng. (Industrial and Systems Engineering))--University of Pretoria, 2018.